DEVELOPMENT OF THE CONCEPT OF POST-CONFLICT PEACEBUILDING IN UKRAINE - Литвин, О. Е. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2020)
The article provides analysis of the general theoretical approaches to the definition of the «post-conflict peacebuilding» concept in global political science. It contains the analysis of the formation and development of the concept by international institutions (the UN and the EU) and individual researchers, considers the features of the concept and the basic definition criteria, highlights several most relevant concepts and approaches. The material actualizes the lack of in-depth research on this topic in the world and in Ukraine. In addition to that, it states the modern problems in the identification and differentiation of concept ‘post-conflict peacebuilding” in the international science. A particular attention was paid to various formulations of the concept of “post-conflict peacebuilding” in Ukraine. The national basis for the research and for the formed concepts, highlighted the principles of creating a definition was examined. The main acquisitions and developments of both sectors on this issue are analyzed, the presence/absence of a clear definition is indicated based on the consideration of governmental documents and statutes/visions of non-governmental organizations. The work identifies the main actors who are involved in the conceptualization of the concept and the promotion of research on the topic. It highlights the documents that mention the problem of peacebuilding. Further to this, it determines the focus of the public sector and indicates the change in the status of Ukraine in the research field. Was made an attempt to determine the practical forms of implementation of the concept in Ukraine. The study determines the mechanisms and forms of testing the concept of post-conflict peacebuilding in Ukraine in practice. Additionally, was assembled a list of organizations that are actively involved in developing the modern concept of post-conflict peacebuilding in Ukraine. The study indicates that introducing an integrated approach for analyzing the problem, coordinating the state and non-state sectors on the issue of peacebuilding is essential. It provides the problems and shortcomings of the research and testing methods. Besides, the paper determined the perspectives for further research on the issue of post-conflict peacebuilding.